2011
DOI: 10.4161/cc.10.9.15486
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase: Its role as a cancer stem cell marker comes down to the specific isoform

Abstract: Recent evidence suggests that enhanced aldehyde dehydrogenase (ALDH) activity is a hallmark of cancer stem cells (CSC) measurable by the aldefluor assay. ALDH1A1, one of 19 ALDH isoforms expressed in humans, was generally believed to be responsible for the ALDH activity of CSCs. More recently, experiments with murine hematopoietic stem cells, murine progenitor pancreatic cells, and human breast CSCs indicate that other ALDH isoforms, particularly ALDH1A3, significantly contribute to aldefluor positivity, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
417
3
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(439 citation statements)
references
References 79 publications
12
417
3
7
Order By: Relevance
“…These vary depending on the cancer, and not all tumor cells identified by certain markers are cancer stemlike cells/tumor-initiating cells. 46 In this study, 18%, 10% and 9% of the upper urinary tract urothelial cell carcinoma cases had ALDH1 pos SOX2 neg , ALDH1 neg SOX2 pos and ALDH1 pos SOX2 pos tumor (Table 2). Furthermore, the number of upper urinary tract urothelial cell carcinoma cells immunohistochemically stained for both ALDH1 and SOX2, which are considered to have more characteristics of cancer stem-like cell/tumorinitiating cell, was limited in these cases (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 52%
“…These vary depending on the cancer, and not all tumor cells identified by certain markers are cancer stemlike cells/tumor-initiating cells. 46 In this study, 18%, 10% and 9% of the upper urinary tract urothelial cell carcinoma cases had ALDH1 pos SOX2 neg , ALDH1 neg SOX2 pos and ALDH1 pos SOX2 pos tumor (Table 2). Furthermore, the number of upper urinary tract urothelial cell carcinoma cells immunohistochemically stained for both ALDH1 and SOX2, which are considered to have more characteristics of cancer stem-like cell/tumorinitiating cell, was limited in these cases (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 52%
“…A subset of ALDH isoforms, most notably ALDH1A1, has been found to be upregulated in somatic and CSCs and may play roles in the detoxification of aldehydes, retinoic acid signalling and other cellular processes (Marcato et al 2011). A fluorescent substrate of ALDH, Aldefluor, allows the identification and purification of ALDH1-expressing cells (Storms et al 1999).…”
Section: Aldefluormentioning
confidence: 99%
“…Aldehyde dehydrogenase (ALDH) enzymes catalyse the oxidation of aldehydes into carboxylic acids and are encoded by 19 different isoforms in human (Marcato et al 2011). A subset of ALDH isoforms, most notably ALDH1A1, has been found to be upregulated in somatic and CSCs and may play roles in the detoxification of aldehydes, retinoic acid signalling and other cellular processes (Marcato et al 2011).…”
Section: Aldefluormentioning
confidence: 99%
See 1 more Smart Citation
“…30,68 Todaro et al showed that PTC, FTC and ATC contain a small population of tumourigenic cells with high ALDH activity and unlimited replication potential. Expanded indefinitely in vitro as tumour spheres, these ALDH high cells contain 25-60% of the clonogenic cells able to generate serial tumour xenografts.…”
Section: Thyroid Cancer Stem Cellsmentioning
confidence: 99%